PROBLEM SOLVING APPLIED IN THE THEORY OF NUMBERS IN DIVISIBILITY CONTENT - Lacerda, Amanda; Oliveira, Laryssa (Journal of Interdisciplinary Debates, 2022)
This work aims to show crucially the way in which education, especially mathematics, has evolved in terms of learning methods over time, according to the charter of the respective societies. Among the methods that were addressed in the work, Problem Solving stands out, based on the perspectives of Polya and Allevato, a powerful tool for the evolution and establishment of knowledge, reasoning, autonomy and student investigation. The methodology used was qualitative with a literature review, and the results showed the importance of problem solving for the understanding of divisibility and also of other concepts worked on in mathematics.